ANALISIS FLYPAPER EFFECT DARI DANA ALOKASI UMUM (DAU), PENDAPATAN ASLI DAERAH (PAD) DAN SATUAN KERJA PERANGKAT DAERAH (SKPD ) TERHADAP BELANJA DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TIMUR TAHUN 2015-2019 - Indah Ningsih; Anik Malikah; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The implementation of fiscal decentralization and regional autonomy policies has been implemented since early 2001, where the central government transferred authority to regional governments to optimize and manage their regional potential. The implementation of this policy has several problems, one of which is differences of opinion in the use of the balancing fund. For this reason, this study aims to determine the effect of General Allocation Fund (DAU), Regional Original Income (PAD) and Regional Work Unit Financial Reports (SKPD) on District / City Regional Expenditures in East Java Province 2015 to 2019, using Purposive sampling technique and use multiple linear regression analysis with Statistical Package for Social Sciences (SPSS), the data used is secondary data from relevant data sources. The results showed that there was no flypaper effect on regional spending. The general allocation fund, regional revenue, and regional work units significantly influence regional spending.Keywords: flypaper effect, general allocation funds, local revenue, regional work units, regional spending.